POLIGAMI DALAM PERSPEKTIF HADITS - Puspita, Era (Jurnal Ar-Risalah, 2021)
This article leads to the quality of the hadith and the meaning of the hadith. In collecting data, the library research method is used and in reviewing the data using the takhrij hadith method, the validity of the sanad and matan as well as the theory of hadith meaning. This hadith research on polygamy results in the quality of the hadith being Sahih li dzatihi. The hadith can be used as evidence because the hadith ma'muluun wa maqbuluun, which has met the criteria for blasphemy and authenticity of the hadith. The validity of the Matan hadith does not conflict with the Qur'an, with the Hadith and reason. The hadith discusses the implications of each polygamy that is carried out including polygamy with a maximum of four wives and in polygamy there are rights and obligations that must be fulfilled by husbands to wives, namely collecting and rotating their wives fairly, with love and maintenance. Polygamy is not something that has just emerged but after Islam came, polygamy was directed and regulated by human and noble rules, therefore this practice is not a disgraceful or negative thing as long as someone wants to do polygamy with a clear purpose and fulfills all the provisions that have been made. regulated by religion. Islam does not necessarily allow the practice of polygamy but if polygamy is carried out with negative and unclear purposes, then Islam opposes and prohibits this practice strictly with the intention of maintaining the status of women.